2001
DOI: 10.3171/spi.2001.94.2.0205
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in adults with tethered cord syndrome: outcome study with independent clinical review

Abstract: Object. The authors conducted a study to evaluate the risks and short-term benefits of surgical treatment for tethered cord syndrome (TCS) in patients older than 18 years of age. Methods. The authors studied a series of 57 consecutive adult patients with TCS of varying origins. Patients were examined by the same neurologist in a standardized fashion before and after surgery, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 17 publications
(16 reference statements)
0
48
0
Order By: Relevance
“…More recently, McLone 28 described 3 categories: 1) those who were previously asymptomatic presenting with signs and symptoms of cutaneous stigmata; 2) the true occult group presenting with signs and symptoms and no cutaneous stigmata; and 3) those with a previous diagnosis of spinal dysraphism, with or without a detethering or repair procedure, with stable or progressive deficits.As stated previously, the adult presentation of TCS is similar to that in adolescent patients, with back or leg pain as a predominant feature. 18,25,31,36,42 The pain is most often nondermatomal, shocklike, or with a burning quality. Mostly the pain is insidious, but may present with acute onset or aggravation of existing pain.…”
Section: Adult Presentation Of Tcsmentioning
confidence: 99%
“…More recently, McLone 28 described 3 categories: 1) those who were previously asymptomatic presenting with signs and symptoms of cutaneous stigmata; 2) the true occult group presenting with signs and symptoms and no cutaneous stigmata; and 3) those with a previous diagnosis of spinal dysraphism, with or without a detethering or repair procedure, with stable or progressive deficits.As stated previously, the adult presentation of TCS is similar to that in adolescent patients, with back or leg pain as a predominant feature. 18,25,31,36,42 The pain is most often nondermatomal, shocklike, or with a burning quality. Mostly the pain is insidious, but may present with acute onset or aggravation of existing pain.…”
Section: Adult Presentation Of Tcsmentioning
confidence: 99%
“…Despite the management of congenital TCS diagnosed in adulthood remains controversial, results of recent clinical studies of surgical intervention in adults are encouraged (7,9,12,14,19). The question here, how can neurosurgeons manage this complex entity to protect the patients from new deficits and keep their neurological functions intact?…”
mentioning
confidence: 99%
“…25 George and Fagan 25 found only 7 case reports and case series reporting clinical experiences with this condition up through 2003. 21,52,65,67,74,79,82 The magisterial 1982 paper by Pang and Wilberger 67 on tethered spinal cord in adults includes a single patient with a sacral myelomeningocele who was investigated using metrizamide CT myelography. In addition to tethering at the site of the repair, this patient had a tight filum terminale.…”
Section: Spinal Cord Tetheringmentioning
confidence: 99%
“…Twelve patients had undergone tethered cord release, but the ages at which this intervention was performed were not stated. Van Leeuwen et al 82 reported a large institutional series of adults operated for tethered cord syndrome that included 12 patients with myelomeningocele and secondary tethering. Three of 12 patients enjoyed postoperative improvements of 1 or 2 points on a modified Rankin Scale; no other data specific to myelomeningocele were reported.…”
Section: Spinal Cord Tetheringmentioning
confidence: 99%